Geliat Tafsir ‘Ilmi di Indonesia dari Tafsir Al-Nur hingga Tafsir Salman - Annas Rolli Muchlisin; Khairun Nisa (Institut Agama Islam Negeri (IAIN) Salatiga, 2017)
This article discusses a long journey of ‘ilmi interpretation in Indonesia since the era of 1960s until now. The author concerns at how the interpretation with this style is transformed along with the rapid development of science and technology. Although the debate over the status of ‘ilmi interpretation is never end, at least the scholars are divided into three groups: the advocates, the rejectionists, and the moderates, but this interpretation continues to emerge in different parts of Muslim countries, including Indonesia. Since the 1960s, the ‘ilmi interpretation embryo had appeared in several works of Nusantara’s Mufassir. This embryo then developed in the era of the 1990s with the outbreak of books that explained the relation of al-Qur’an and science. This stage was growing again in the year 2010s in the form of intact interpretation work. This study shows that the dynamics of ‘ilmi interpretation journey in Indonesia are very dynamic.